BREEDING OF A PENAEID PRAWN, METAPENAEUS DOBSONI IN THE BRACKISH WATER MEDIUM - Rao, P Vedavyasa; Kathirvel, M (Indian Journal of Fisheries, 2011)
Laboratory spawning of a mature female Metapenaeus dobsoni obtainedfrom the Cochin Backwater and kept in the brackish water medium (salinity30.22%o, temperature IT.S'C) is reported. The eggs reared in the brackishwater medium hatched out into nauplii, but none of them developed further.On transferring a few nauplii to the sea water (salinity 34.02%o) after two days,they transformed into abnormally developed protozoeae. The importance of this -observation in the context of breeding of Indian penaeid prawns and from thepoint of view of their culture in the coastal estuaries is pointed out.